Physicochemical stability of Cabazitaxel Zentiva® solution in vials after opening and diluted solutions in three infusion bags - D'Huart Elise; Sacrez Matthieu; Vigneron Jean; Sobalak Nathalie; Demoré Béatrice (De Gruyter, 2023)
To the best of our knowledge, few studies have been published on the stability of cabazitaxel in infusion bags. Stabilis® database has selected a study demonstrating the stability of this molecule at 0.15 mg/mL for 28 days at 4 °C and 25 °C in polyolefin bags. The aim of this work was to study the physicochemical stability of Cabazitaxel Zentiva® solutions in vials after "opening" with a vented ChemoClave® Spike, at 25 °C, protected from light and in solutions diluted at 0.1 and 0.26 mg/mL in 0.9 % sodium chloride (0.9 % NaCl) or dextrose 5 % (D5W) in 3 types of infusion bags (Easyflex® and Viaflo® at 25 °C, Freeflex® between 2 and 8 °C, protected from light).